Halo mass estimates from the globular cluster populations of 175 low surface brightness galaxies in the Fornax cluster - Prole, Daniel J.; Wittmann, Carolin (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. The halo masses Mhalo of low surface brightness (LSB) galaxies are critical measurements for understanding their formation processes. One promising m
Gesehen am 18.02.2019